Characteristics and genesis of montmorilonitic claystone from Bandung area, Wonosegoro, Boyolali, Central Java, Indonesia - Anita Yuliyanti; I Wayan Warmada; Anastasia Dewi Titisari (Journal of Applied Geology, 2015)
The Bandung bentonite deposit is located in Wonosegoro District, Boyolali Regence, Central Java. Characteristics of bentonite in this area are very important due to increase demand on bentonite in the industry. Several methods are used to characterize the bentonite in this area, such as PLM (polarizing light microscope), X-Ray Diffraction and Scanning Electron Microscope combined with EDX measurements. The montmorilonitic claystone belongs to Kerek Formation from Banyuurip Member. This deposit consists of mainly montmorilonitic claystone interbedded with tuffaceous sandstone. Petrographical analysis shows that montmorilonitic claystone consists of mostly clay minerals with small amount of calcite, volcanic glass, feldspar, quartz, and opaque minerals. The clay minerals are likely as alteration product of volcanic glass. The oriented XRD analyses show that the clay samples consist of Ca-montmorilonite, illite, and kaolinite. Physico-chemical analyses of montmorilonitic claystone display that the initial CEC (cation exchange capacity) is 20 mgrek.Na2O/200gr (54 mg.Na2O/100gr) and low swelling ability for about 2 times of its initial volume. Based on its mineralogical association, textures, and stratigraphic position, the montmorilonite is formed from devitivication of volcanic glass in a diagenetic environment with over 2 km thicks of overburden. Keywords: Bentonite, montmorillonitic claystone, devitrivication, diagenesis, montmorillonite